Peningkatan Kemampuan Mengenal Lambang Bilangan 1 Sampai 10 Melalui Vidio Pembelajaran Animasi Bagi Anak Disabilitas Intelektual Ringan - Sijabat, Savendi; Iswari, Mega; Nurhastuti , Nurhastuti; Taufan, Johandri (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to improve the ability to recognize number symbols from 1 to 10 through the use of animated learning videos for children with mild intellectual disabilities. The research employed a Classroom Action Research (CAR) method conducted at SLB Negeri Simalungun. The research subjects consisted of three students with mild intellectual disabilities, identified by the initials RP, RS, and K. Based on the initial assessment, the students’ ability to recognize number symbols was categorized as low, with achievement percentages of 20% for RP, 30% for RS, and 40% for K. The study was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The results of observations in Cycle I showed an improvement in students’ ability to recognize number symbols, with RP achieving 50%, RS 60%, and K 60%. Furthermore, in Cycle II, students’ abilities increased significantly, with RP reaching 80%, RS 90%, and K 90%. Data were collected through observation using an assessment sheet of number symbol recognition skills, while data analysis was conducted using descriptive quantitative analysis by comparing the results between cycles. The findings indicate that animated learning videos are effective in improving the ability to recognize number symbols from 1 to 10 among children with mild intellectual disabilities. This study confirms that the use of engaging and visual learning media that align with the learning characteristics of children with mild intellectual disabilities can effectively enhance students’ attention, understanding, and learning outcomes.